An exploration of the attitudes and views of general practitioners on the use of video consultations in a primary healthcare setting: a qualitative pilot study. (18th June 2019) - Randhawa, Ratan S.; Chandan, Joht S.; Thomas, Tom; Singh, Surinder
Abstract: Background: In 2014, in the United Kingdom, the government made a commitment to spend £3.6 million on the introduction of Skype video calling consultations in general practice, however the efficacy of such technology has not yet been explored fully. Aim: The study aimed to explore the views and attitudes of General Practitioners (GPs) towards video consultation in primary care; specifically, in three broad areas ∙ The benefits of video consultations to patients and healthcare professionals. ∙ Potential problems with video consultation and its implementation. ∙ The cost-effectiveness of video consultation in this setting. Method: A convenience sample of the views of 12 general practitioners across two primary care centres in North London were identified using topic guide based semi-structured interviews. A thematic framework approach was used to analyse the data collected to isolate main and sub-themes. Findings: Three main themes were identified 1. Technology – GPs expressed concerns about the ability of patients to use technology, the availability of technology and the quality of technology available. 2. Utility – encompassing GP's ideas about the usefulness of video consultations to patients, practitioners and the doctor–patient relationship. GPs presented mixed views on the extent to which video consultation would be useful. 3. Practicality – covering the views of GPs on implementation and effects on workload. GPs unanimously felt that it was not a practical substitute for face-to-face consultation. There were mixed feelings about it being used as an alternative to telephone consultation. Conclusion: GPs did see potential benefits to using video consultations but also expressed concerns that need to be addressed if they are to have full confidence in the system. The views of those who are going to use video consultation as a means of increasing patient access are paramount if such tools are to be a core part of primary care.